Histopathological spectrum of lung findings in autopsy cases - Prakasam, Gowri; Sadasivam, Brihadisvarar; Rajasekaran, Vallabi; Muniraj, Kavitha; Prathapan, Abikarthiga (Asian Journal of Medical Sciences, 2024)
Background: The incidence of lung pathology is the most common autopsy finding and is responsible for a great deal of mortality and morbidity. It is affected by a wide variety of respiratory pathogens and is involved in many systemic diseases. It is secondarily involved in almost all forms of terminal disease. Radiological findings are usually nonspecific in lung diseases and need prompt histopathological examination to find out the exact cause of death. Aims and Objectives: The aim is to study the spectrum of histopathological findings in lung in autopsy cases. Materials and Methods: This is a retrospective study done in the Department of Pathology at Government Kilpauk Medical College and Hospital during the year 2022. Lung specimens were received from the Forensic medicine department. Gross findings were noted. Following adequate formalin fixation, the tissue specimens were processed and paraffin sectioning was done followed by hematoxylin and eosin staining. The findings were documented and the results were analyzed. Results: Among 100 cases studied during year maximum cases were seen in the age group of 31–40 years (32%). Males (72%) were more commonly affected than females (28%). The most common findings are Pulmonary edema (34%) followed by congestion (32%) and other findings include emphysematous change (13%), pneumonia (10%), tuberculosis (6%), metastatic adenocarcinomatous deposits (1%), primary well-differentiated adenocarcinoma (1%), pulmonary chondroma (1%), and bronchiectasis (1%). Conclusion: The most common finding observed was pulmonary edema. In our study, male preponderance was noted. This study emphasizes to scrutinize the histopathological findings in the lung, especially following a sudden death.